Thirty-Year Trends (1991-2020) in Breast Cancer Incidence Rates: Hanoi, Vietnam - Giang Nguyen Huong; Hoa L. Nguyen; Robert J. Goldberg; Mara M. Epstein; Jeroan J. Allison; Loc Quang Pham; Le Minh Giang; Sang Minh Nguyen; Ngoc Dac Nguyen; Linh Thi Thuy Nguyen; Quang Le Van; Thuan Tran Van; et al. (JCO Global Oncology)
PURPOSEBreast cancer is the most common cancer in Vietnam, yet there are limited data on long-term trends and factors influencing its incidence. This study examines 30-year trends (1991-2020) in breast cancer incidence among women in Hanoi, focusing on age, period, and cohort effects.METHODSData from 28,298 breast cancer cases registered in the Hanoi Cancer Registry between 1991 and 2020 were analyzed. Trend analysis using Joinpoint regression was performed to calculate the average annual percent change (AAPC) in incidence rates, and an age-period-cohort analysis was used to explore underlying trends.RESULTSThe age-standardized incidence rate of breast cancer rose from 15.2 per 100,000 in 1991 to 40.6 per 100,000 in 2020, with an overall AAPC of 4.1% (95% CI, 2.9 to 5.4). Women age 70 years and older experienced the highest increase (AAPC, 6.4% [95% CI, 2.5 to 10.4]) compared with those age 40-49 years (AAPC, 2.6% [95% CI, 2.1 to 3.1]). Incidence rates during 2016-2020 were 1.6 times higher than in 2001-2005. Women born between 1976 and 1980 exhibited significantly higher incidence rates compared with earlier cohorts.CONCLUSIONBreast cancer incidence in Hanoi has more than doubled over three decades, with significant age, period, and cohort effects. These findings provide insights for the development of targeted breast cancer control strategies, including tailored screening, prevention efforts, and resource allocation to address the growing burden of this disease in Vietnam.